1994
DOI: 10.1136/jnnp.57.11.1436-a
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalaemia mimicking acute Guillain-Barre syndrome.

Abstract: Recurrent confusion and ataxia triggered by pyrexia in a case of occult multiple sclerosis It has long been known that an increase in body temperature may worsen reversibly the signs and symptoms of multiple sclerosis, probably by the production of conduction block in partially demyelinated nerve axons. We present the case of a man whom we believe has multiple sclerosis, who has a nine year history of brief episodes of profound neurological dysfunction, always in association with pyrexial illnesses. The unusua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 2 publications
1
11
0
1
Order By: Relevance
“…Although the precise mechanism of secondary hyperkalemic paralysis remains unclear, the persistent state of depolarization in the neurons is believed to be responsible for the reversible neuromuscular paralysis. It manifests clinically with an ascending pattern, from the lower extremities followed by a progression into the trunk and arms closely resembling the Guillian Barré syndrome [1,2]. In our patient, as well as most of other cases in the literature, there was no compromise of respiratory muscles, cranial nerves or sphincter tone [3].…”
Section: Case Presentationsupporting
confidence: 67%
“…Although the precise mechanism of secondary hyperkalemic paralysis remains unclear, the persistent state of depolarization in the neurons is believed to be responsible for the reversible neuromuscular paralysis. It manifests clinically with an ascending pattern, from the lower extremities followed by a progression into the trunk and arms closely resembling the Guillian Barré syndrome [1,2]. In our patient, as well as most of other cases in the literature, there was no compromise of respiratory muscles, cranial nerves or sphincter tone [3].…”
Section: Case Presentationsupporting
confidence: 67%
“…3 Cerebrospinal fluid has been examined in four patients and has been normal in every case 23 9Most cases described earlier have had an onset of muscle weakness over days. In our patient, the muscle weakness was more abrupt in onset.…”
Section: Discussionmentioning
confidence: 98%
“…3 5 8 In two cases where neurophysiological studies have been carried out, reduced nerve conduction velocities have been found suggesting nerve mediated weakness 23 Cerebrospinal fluid has been examined in four patients and has been normal in every case 23 9Most cases described earlier have had an onset of muscle weakness over days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of paralysis resembles the one that is observed in Guillain-Barre Syndrome [12, 13]. It has been reported that this entity has been observed in patients with end-stage renal disease on hemodialysis or it has been precipitated as a result of antibiotic therapy [7] or in the context of drug use and abuse [6, 8].…”
Section: Discussionmentioning
confidence: 67%